"Time Variable Earth Gravity Field Models From the First Spaceborne Laser Ranging Interferometer". Issue 12 (20th December 2021) - Pie, N.; Bettadpur, S. V.; Tamisiea, M.; Krichman, B.; Save, H.; Poole, S.; Nagel, P.; Kang, Z.; Jacob, G.; Ellmer, M.; Fahnestock, E.; Landerer, F. W.; et al.
Abstract: The Gravity Recovery and Climate Experiment Follow‐On (GRACE‐FO), launched May 22, 2018 and collecting science data since June 2018, is extending the 15‐year data record of Earth mass change established by its predecessor GRACE mission (2002–2017). The GRACE‐FO satellites carry onboard a novel technology demonstration instrument for intersatellite ranging, the Laser Ranging Interferometer (LRI), in addition to the microwave interferometer (MWI) carried on GRACE. The LRI has out‐performed its in‐orbit performance requirements both in terms of accuracy as well as the duration of tracking. Here, we compare and validate LRI‐based gravity solutions for January 2019 to September 2020 against the MWI solutions. The comparison between the two sets of gravity solutions shows great similarities in general and nearly perfect consistency at a large hydrologic basin spatial scale (100, 000 km 2 and above), commonly viewed as the spatial resolution established by GRACE. The comparison in the spectral domain shows differences at the higher degrees of the spectrum, with lower error in the zonal and near zonal terms for the LRI solutions. We conclude that the LRI observations can be used to recover time‐varying gravity signals to at least the level of accuracy established by the MWI‐based solutions. This is a promising finding, especially when considering the benefits of using the LRI over the MWI, such as the great stability of the instrument and the low occurrence of instrument reboot events. Plain Language Summary: The Gravity Recovery and Climate Experiment was a mission consisting of a pair of satellites flying in tandem, one following the other along the same orbit, between 2002 and 2017. Onboard the satellites were specialized instruments that used microwaves to measure the changes in the distance between the two satellites. Using those observations, it is possible to infer the changes in the Earth's gravitational pull, hence in the distribution of its mass and more specifically, its water mass. During the mission's 15‐year lifetime, the global scientific community has come to rely on these observations for monitoring the Earth's ice sheets, oceans, droughts, and floods. Its successor mission, the Gravity Recovery and Climate Experiment Follow‐On, is based on the same mission concept. In addition to the microwave instrument, it also includes a novel instrument that uses a laser beam to measure the distance between the satellites. We present a comparison between the Earth's gravity information retrieved from either instrument and their respective quality levels. We conclude that the novel laser instrument performs as well as the microwave instrument for the retrieval of gravity information and that it is a good candidate for future satellite gravity missions. Key Points: Gravity solutions are estimated from the laser ranging interferometer observations on board the Gravity Recovery and Climate Experiment Follow‐On satellites Some modifications are needed when applying estimation procedures initially developed for the microwave interferometer to this new observation type These new gravity solutions are comparable to the gravity solutions derived from the microwave interferometer observations at 270 km spatial scale